2015
DOI: 10.1007/s11910-015-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Update on Cysticercosis Epileptogenesis: the Role of the Hippocampus

Abstract: Neurocysticercosis (NCC) is the most common helminthic infection of the nervous system and a frequent cause of reactive seizures and epilepsy worldwide. In many cases, multiple episodes of focal seizures related to an identifiable parenchymal brain cyst (and likely attributable to local damage) continue for years after the cyst resolves. However, cases where seizure semiology, interictal EEG abnormalities, and parasites location do not correlate raise concerns about the causal relationship between NCC and eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 52 publications
5
75
0
1
Order By: Relevance
“…[4][5][6][7] However, it is not yet clear whether this association is related to repetitive seizure activity or to mechanisms of local or remote inflammation. [8][9][10] We recently reported the association between calcified NCC and hippocampal atrophy in a population of 248 older adults living in rural Ecuador. 11 This report expands the studied population to 663 individuals, including 318 aged 40-59 years, to explore whether this association persists at a younger age.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] However, it is not yet clear whether this association is related to repetitive seizure activity or to mechanisms of local or remote inflammation. [8][9][10] We recently reported the association between calcified NCC and hippocampal atrophy in a population of 248 older adults living in rural Ecuador. 11 This report expands the studied population to 663 individuals, including 318 aged 40-59 years, to explore whether this association persists at a younger age.…”
Section: Introductionmentioning
confidence: 99%
“…[12] This case wherein follow-up neuroimaging studies have revealed the development of HS 2 years after the diagnosis of NCC lends support to the hypothesis that NCC can be a causative factor in the development of HS and potential mechanism seems to be inflammation-mediated and not recurrent seizures. Another unusual finding, in this case, has been nondevelopment of refractory epilepsy despite the presence of HS.…”
mentioning
confidence: 59%
“…Additionally, multiple reports suggest that NCC may lead to mesial temporal sclerosis as a secondary epileptogenic focus. 5659 Repeated focal seizures along years or even decades in patients with NCC suggest a structural damage and formation of epileptogenic circuits, independent of the contributory effect of transient episodes of inflammation.…”
Section: Neurocysticercosis and Epilepsymentioning
confidence: 99%